Stable and Efficient PtRu Electrocatalysts Supported on Zn-BTC MOF Derived Microporous Carbon for Formic Acid Fuel Cells Application - Khan, Inayat Ali; Sofian, Muhammad; Badshah, Amin; Khan, Muhammad Abdullah; Imran, Muhammad; Nadeem, Muhammad Arif (Frontiers in Chemistry, 2020)
Highly efficient, well-dispersed PtRu alloy nanoparticles supported on high surface area microporous carbon (MPC) electrocatalysts, are prepared and tested for formic acid oxidation reaction (FAOR). The MPC is obtained by controlled carbonization of a zinc-benzenetricarboxylate metal-organic framework (Zn-BTC MOF) precursor at 950°C, and PtRu (30 wt.%) nanoparticles (NPs) are prepared and deposited via a polyol chemical reduction method. The structural and morphological characterization of the synthesized electrocatalysts is carried out using powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), an energy dispersive X-ray (EDX) technique, and gas adsorption analysis (BET). The FAOR performance of the catalysts is investigated through cyclic voltammetry (CV), chronoamperometry (CA), and electrochemical impedance spectroscopy (EIS). A correlation between high electrochemical surface area (ECSA) and high FAOR performance of the catalysts is observed. Among the materials employed, Pt1Ru2/MPC 950 with a high electrochemical surface area (25.3 m2 g−1) consequently showed superior activity of the FAOR (Ir = 9.50 mA cm−2 and Jm = 2,403 mA mgPt-1) at room temperature, with improved tolerance and stability toward carbonaceous species. The superior electrochemical performance, and tolerance to CO-poisoning and long-term stability is attributed to the high surface area carbon support (1,455 m2 g−1) and high percentage loading of ruthenium (20 wt.%). The addition of Ru promotes the efficiency of electrocatalyst by offering FAOR via a bifunctional mechanism.